Proposta de gerenciamento de stakeholders segundo processos do PMBOK: um estudo sobre eventos editoriais no Estado de S??o Paulo - Eduardo, Val??ria Vanessa (2015)
According to research conducted in 2013 by the Brazilian Book Chamber and the Economic Research Foundation, the publishing industry showed a nominal increase of 7.52% over the previous year. This increase accounts for the copies produced electronically and in hardcopy as well as the numbers of sales in the period. Another significant point of the research, both for the editorial stage as to an analysis of the reading of the Brazilian citizen profile, is the amount of new titles available. In 2012, there were 51,905 new works by national authors. This indicator increased by almost 10% to 56,372 in 2013. Together the information, we see a positive outlook for literature, with several opportunities for publishing. It is presented to publishers the challenge of conquering a readership growing. Thus, the editorial events appear as strategic projects to attract readers. In this context, this study aims to how stakeholders are managed in editorials events projects, considering the project management processes proposed by PMBOK. Project management has been established as an important tool in the strengthening of the results of the events, since the benefits from the use of planning, execution and control of temporary and unique events prove to be perfectly adherent to event management. Whereas the stakeholder management process aims to engage them, aspect of fundamental importance for success in project management, through a qualitative approach whose strategy will be a multiple case study in S??o Paulo, this study presents as result in a proposal of key activities related to the management of stakeholders from project management processes that are applicable to events that meet the demands of the publishing market.